Effectiveness of nutmeg flesh extract (Myristica fragrans H) as an immunomodulator using the carbon clearance method in mice (Mus musculus) - Rokhmah, Nisa Najwa; Herlina, Nina; Ananda, Syindi Yulia (JURNAL ILMU KEFARMASIAN INDONESIA, 2024)
Nutmeg (Myristica fragrans H) is composed of secondary metabolite compounds, among which flavonoids significantly contribute to its immunomodulatory properties. Using the carbon clearance method, this study aims to determine the efficacy of nutmeg flesh extract (NFE) as an immunomodulator. Negative control (Na-CMC 0.5%), normal control (Na-CMC 0.5%), immunostimulant positive control (Imboost® Force 0.91mg/20 g BW of mice), immunosuppressant positive control (methylprednisolone® 0.015 mg/20 g BW of mice), dose I (5 mg/20 g BW of mice), dose II (10 mg/20 g BW of mice), and dose III (20 mg/20 g BB mice) comprised the seven groups of 35 white male mice (DDY). The assessed parameters included organ index, absorbance, and the phagocytosis constant and index. The immunostimulant effect of NFE was demonstrated by the phagocytosis index values of 1.225 (indicating moderate immunostimulation), 1.512 (indicating moderate immunostimulation), and 2.202 (indicating strong immunostimulation) for NFE dose I, II, and III, respectively. The lymphoid organ index may have increased among the three NFE treatment groups, according to the results of organ index measurements. We can conclude, Nutmeg Flesh Extract (NFE) has an immunomodulatory effect in the immunostimulant category, as well as increased phagocytosis activity and lymphoid organ index.